Pengaruh Carburizing Arang Tulang Sapi Terhadap Peningkatan Kekerasan Egrek Produk Pande Besi Desa Tanjung Pinang - Sailon, Sailon; Seprianto, Dicky; Andika, Ekki (Politeknik Negeri Sriwijaya, Indonesia, 2022)
The egrek must have a tough hardness in the eyes of the egrek, but the craftsman there is criticism by consumers regarding the quality of his sharpness and toughness, therefore. The purpose of this study is to determine the effect of carburizing cow bone charcoal on increasing the egrek hardness of blacksmith products in Tanjung Pinang Village. This research method is a pack carburizing experiment using cow bone charcoal with temperature variations of 850°C, 900 °C, and 950°C and a containment time of 30 minutes, 45 minutes, and 60 minutes. The results of this study prove that the composition of the egrek material of blacksmith products with an elemental carbon value of 0.414% and pack carburizing using cow bone charcoal affects the hardness, the top surface hardness value at a temperature variation of 950°C with a 60-minute containment time of 59.2 HRC. Temperature is very influential in carrying out pack carburizing against the increase in surface hardness.